Homo Novus - A Human Without Illusions - Frey, Ulrich J.; Störmer, Charlotte; Willführ, Kai P. (The Frontiers Collection,, 2010)
Converging evidence from disciplines including sociobiology, evolutionary psychology and human biology forces us to adopt a new idea of what it means to be a human. As cherished concepts such as free will, naïve realism, humans as creation's crowning glory fall and our moral roots in ape group dynamics become clearer, we have to take leave of many concepts that have been central to defining our humanness. What emerges is a new human, the homo novus, a human being without illusions. Leading authors from many different fields explore these issues by addressing these illusions and providing evidence for the need to switch to this new idea of man, in spite of understandable reluctance to let go of our most beloved illusions.